Social Changes and Ecological Records in Poet Vairamuthu’s Third World War Novel - S, Hemalatha (International Research Journal of Tamil, 2022)
Ever since the inception of Novel, its subject matter revolves around man and the society in which he lives. When Novels were dealing with human life and reflecting every facet of history, came poet Vairamuthu’s ’Moondram Ulaga Por’ discussing Globalization, Global warming and hurdles which are to be faced in the coming decades. This novel emphasis on the current farmer issues, water conservation ideas, protecting agricultural lands, the means by which people could take measures against global warming, the responsibility of every individual and society together with a note of warning. Emily and Ishimura being the central characters, this novel covers the issues across the globe from America’s Louisiana Shore to Japan’s Sendai Beach along with the chemical leakage in Karuthammaye well in Attanampatty village in Theni. The objective of this dissertation is to depict that the novel Moondram Ulaga Por insists the need to safeguard environment and to bring about the changes in the agriculture and gives the entire mankind a sheer warning to awake and the changes to be experienced by the posterity also shows how the world is amazed at the knowledge, wisdom and hardwork of Tamil people.